Plant density and nitrogen fertilization in Swiss chard - Echer, Marcia de M.; Zoz, Tiago [UNESP]; Rossol, Charles Douglas; Steiner, Fabio [UNESP]; Castagnara, Deise D.; Lana, Maria do C. (Assoc Brasileira Horticultura, 2012)
An experiment was conducted to evaluate the effect of plant spacing and nitrogen fertilization on Swiss chard's yield, from September to November 2009. The experimental design was of randomized blocks in split plot with four replications. In the plots were allocated the two plant spacings (0.30 and 0.50 m) and in the subplots the five doses of nitrogen (0, 40, 80, 120 and 160 kg ha(-1)). The crop was harvested 90 days after transplanting. The plant spacing of 0.50 m provided increased production of total fresh weight of shoot (961.7 g plant(-1)) and marketable (873.1 g plant(-1)). However, the highest total yield (77.8 t ha(-1)) and marketable (64.5 t ha(-1)) was achieved with the smaller spacing between plants (0.30 m). The N rates applied in coverage until 160 kg ha(-1) increased in a linear form the total and marketable production of fresh mass of shoots, the total and marketable yield, the N content and the N accumulation in the shoots of Swiss chard plants on the evaluated plant spacings.
Densidade de plantio e adubação nitrogenada em acelga
Keywords: Beta vulgaris var. cycla; nitrogen; yield